Prescribing pattern of proton pump inhibitors in the management of acid peptic disorders, focus on ilaprazole - Mayabhate, Mayur M. (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Acid peptic disorders (APDs) result from characteristic but overlapping pathogenic mechanisms that involve acid effects on diminished mucosal defense. Proton pump inhibitors (PPIs) have become a mainstay in the APDs. This survey was aimed to determine the usage profile of different proton pump inhibitors and overall physicians’ opinion about the clinical experience with newer PPI, ilaprazole. Methods: This survey was based on the clinical experience of 107 randomly selected physicians on an aggregate patient basis in the management of acid-peptic disorders from different parts of India. A data report form (DRF) comprising of various questions was answered by these physicians. The responding physicians answered the DRF of patients who suffered from acid-peptic disorders and were eligible for PPI therapy. A minimum of 50 patients per physician were evaluated in this survey. Results: The commonly encountered APD in physicians’ clinical practice were gastroesophageal reflux disorder (GERD) followed by non-ulcer disease. 58.88% physicians highlighted the prevalence of night time symptoms of APD reported by the patients. About 1/4th physicians were of the opinion that long-acting PPIs would be the preferred to offer 24 hour control of gastric acid secretion thereby controlling the nocturnal symptoms. 63.73% of physicians reported significantly better symptomatic relief with once daily dose of ilaprazole than existing PPIs. Conclusions: This survey highlights the lack of 24 hour acid control in APDs with use of conventional PPIs leading to variety of symptoms, especially at night, seriously hampering the sleep quality. Ilaprazole displays important advantages in the clinical settings, with regard to better probability of extending the inhibition of acid secretion over 24 hours as compared to conventional PPIs.